2010
DOI: 10.1007/s10586-010-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

A cost-benefit analysis of using cloud computing to extend the capacity of clusters

Abstract: In this paper, we investigate the benefits that organisations can reap by using "Cloud Computing" providers to augment the computing capacity of their local infrastructure. We evaluate the cost of seven scheduling strategies used by an organisation that operates a cluster managed by virtual machine technology and seeks to utilise resources from a remote Infrastructure as a Service (IaaS) provider to reduce the response time of its user requests. Requests for virtual machines are submitted to the organisation's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 32 publications
0
31
0
4
Order By: Relevance
“…GTJD is also supported by leading Cloud researchers. Buyya et al (2008Buyya et al ( , 2009Buyya et al ( , 2010 demonstrates how their challenges are met, and their SLA models have been useful in getting their jobs and requirements done. Foster et al (2008) demonstrates how Scientific Workflows can be achieved and fulfill scientific challenges.…”
Section: Cloud Challenges In Business Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…GTJD is also supported by leading Cloud researchers. Buyya et al (2008Buyya et al ( , 2009Buyya et al ( , 2010 demonstrates how their challenges are met, and their SLA models have been useful in getting their jobs and requirements done. Foster et al (2008) demonstrates how Scientific Workflows can be achieved and fulfill scientific challenges.…”
Section: Cloud Challenges In Business Contextmentioning
confidence: 99%
“…Anderton , 2008;Waters, 2008;Hull, 2009Investors Anderton, 2008Waters, 2008;Hull, 2009Popularity Anderton, 2008Waters, 2008;Hull, 2009Valuation Anderton, 2008Waters, 2008;Hull, 2009Innovation Anderton, 2008Waters, 2008;Hull, 2009 Get the job done (GTJD) Buyya et al (2008Buyya et al ( , 2009Buyya et al ( , 2010; Foster et al (2008) Table 2, are designed for strategic levels and are useful for long-term sustainability. However, operational management has a different perspective of core successful elements, since there is a difference in terms of problems and challenges faced by strategic executives and operational staff.…”
Section: Success Factors Papers and Books Consumersmentioning
confidence: 99%
“…Cloud-based EMR systems are likely to attract many US health delivery organsations (Sultan, 2014;Kolakowski, 2010). de Assunção et al (2010) conducted a cost-benefit analysis of cloud-based services over the capability of cluster-based solution. The study found effective performance and response times with lower usage cost when using cloud-based operations.…”
Section: Main Innovations Technological Components With the Key Purposesmentioning
confidence: 99%
“…If the task could not be completed using the resources in the private cloud then additional resources required are acquired from the public cloud service provider. A redirection strategy is used to redirect the tasks to the public cloud scheduler and the tasks are scheduled onto virtual machines in the public cloud [8].…”
Section: Components Of Task Scheduling In a Hybrid Cloud Fig 1: Compomentioning
confidence: 99%